PENERAPAN MEDIA VIDEO BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA 3 SMA NEGERI 8 DENPASAR TAHUN AJARAN 2022/2023: Media, Video, Hindu Religion, Learning Outcomes - Ida Bagus Made Sujana; Ni Nyoman Perni; I Putu Andre Suhardiana (UHN IGB Sugriwa Denpasar, 2023)
Video Based Learning Media has advantages, which are more effective and efficient, and support a more active learning process. The learning process at SMA Negeri 8 Denpasar is currently not as expected because the learning outcomes of class XI IPA 3 SMA Negeri 8 Denpasar have not yet reached the completeness set as it should. The issues that will be discussed include (1) What is the form of application of Video Based Learning Media in Hindu Religious Education and Characteristics in Improving Student Learning Outcomes (2) How are students' responses to the application of Video Based Learning Media in Improving Student Learning Outcomes. This study aims to (1) Know the forms of Application of Video Based Learning Media in Religious and Moral Education Learning (2) Analyze the level of student response to the application of Video Based Learning Media in Improving Student Learning Outcomes. This study uses theory (1) Constructivism Theory (2) Cone of Experience Theory. The subjects of this study included all students of class XI IPA 3 at SMA Negeri 8 Denpasar. Methods of data collection using test methods, interviews and observation. Student value data that has been collected is analyzed quantitatively. The results of the data obtained showed an increase in learning outcomes from cycle I, there were 23 students or 51.1% of students who had not completed and 22 students completed (48.8%) increased in cycle II 45 students completed (100%) and all students received a complete score . Student responses were very positive, they liked video-based learning because it was easy to understand and fun. It is suggested to teachers of Hindu religious education and morals to make Video Based Learning media an alternative choice so as to keep abreast of educational developments.